2021
DOI: 10.1039/d0dt04116e
|View full text |Cite
|
Sign up to set email alerts
|

[Re(CO)3(5-PAN)Cl], a rhenium(i) naphthalimide complex for the visible light photocatalytic reduction of CO2

Abstract: A RHENIUM(I) NAPHTHALIMIDE COMPLEX [RE(CO)3(5-PAN)CL] (RE(5-PAN)); 5-PAN = 1-(1,10-PHENANTHROLINE)-4-NITRO-NAPHTHALIMIDE) WAS SYNTHESIZED AND CHARACTERIZED UTILIZING MALDI-TOF MASS SPECTROMETRY, FT-IR, RAMAN, 1H AND 13C NMR, ELEMENTAL ANALYSIS, ELECTRONIC ABSORBTION AND EMISSION SPECTROSCOPY,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 42 publications
2
12
0
Order By: Relevance
“…Furthermore, liquid phase analysis identified methanol as further reduction product with a remarkable FE of 24 %. While generation of formate/formic acid during electrocatalytic CO 2 reduction is rather common, [21,51,52] the formation of methanol is particularly noteworthy. Although experiments performed in CD 3 CN show no incorporation of deuterium into methanol or formic acid, final proof for the formation of methanol from CO 2 must be obtained by utilization of 13 CO 2 .…”
Section: Electrocatalytic Co 2 Reductionmentioning
confidence: 99%
“…Furthermore, liquid phase analysis identified methanol as further reduction product with a remarkable FE of 24 %. While generation of formate/formic acid during electrocatalytic CO 2 reduction is rather common, [21,51,52] the formation of methanol is particularly noteworthy. Although experiments performed in CD 3 CN show no incorporation of deuterium into methanol or formic acid, final proof for the formation of methanol from CO 2 must be obtained by utilization of 13 CO 2 .…”
Section: Electrocatalytic Co 2 Reductionmentioning
confidence: 99%
“…by incorporating multiple PS units) can improve the quantum efficiency capabilities and the ensuing eT dynamics of the supramolecular dyad. 31 Restricted by the first two design principles, attempts to improve the quantum efficiency of these Re(bpy) dyads has been made by using more strongly absorbing PS units, such as porphyrins, [32][33][34][35][36][37] naphthalimide, 38,39 naphthalene diimide, [40][41][42] and perylene diimide (PDI) 43,44 . Although the photophysical dynamics of these dyads appear fundamentally well-understood, only a handful have been properly evaluated as CO 2 reduction photocatalysts (see supporting information, Table S1).…”
Section: Introductionmentioning
confidence: 99%
“…Although the photophysical dynamics of these dyads appear fundamentally well-understood, only a handful have been properly evaluated as CO 2 reduction photocatalysts (see supporting information, Table S1). [35][36][37][38][39] Recently, we reported on four N-annulated perylene diimide (NPDI) functionalized Re(bpy) dyads as CO 2 reduction electrocatalysts. 45 Our investigation of these Re(bpy)-NPDI dyads revealed that the PS unit (NPDI) functions as an electron-reservoir for Re(bpy), enabling efficient CO 2 reduction at an overpotential 300 mV lower than conventional Re(bpy)-type electrocatalysts.…”
Section: Introductionmentioning
confidence: 99%
“…13 The ligand 5-PAN was prepared as previously reported. 10 [Re(CO) 3 (H 2 O) 3 Br] (0.26 mmol, 105 mg) and 5-PAN (0.26 mmol, 110 mg) were combined in 30 mL MeOH/DCM (1 : 9 v/v), put under argon, and stirred for 1.5 hours. The solution volume was reduced to half in vacuo and diethyl ether was added to precipitate the product.…”
Section: Synthetic Proceduresmentioning
confidence: 99%
“…Catalytic saturation was reached at 0.87 mmol of HCOO À , corresponding to a TN ([HCOO-]/ [1]) of 48. 10 In the present research, we aim to discern a mechanism for the system and improve the photocatalytic ability of 1. We synthesized the bromide analogue, [Re(CO) 3 (1-(1,10)- phenanthroline-5-(4-nitro-naphthalimide)Br] (2), to evaluate the effect of the halide.…”
Section: Introductionmentioning
confidence: 99%